(untitled) (Global Journal of Science Frontier Research, 2022)
Maize (Zea mays L.) is the most abundantly produced and consumed cereal in the world. Major challenge in maize production in Africa is low soil fertility due to lack of sustainable soil fertility restoring inputs among others. This study investigated the potentials of Moringabanana-maize mix, a biodegradable, environment friendly and abundantly available free gifts of nature in soil fertility improvement. The objective of this study was to investigate the effects of the mixture of Moringa olifera leaves (MO) +Banana Peels (BL) +Maize Stalks (MS) on yield and profitability of maize production. Specifically, to choose the right combination of the mix and determine the correct mode of application. Field and screen house experiments were conducted in 2020 planting seasons, at the Teaching and Research Farm of Kwara State University, Malete. Four treatments were considered and each represented a technology on field/screen trials. These include; A=100N+40P+30K, B= 120N+50P+40K, C= 70N+30P+ 20K and the control using the national recommended dose of 90kg/ha of NPK fertilizer (for comparison).